1981
DOI: 10.6028/jres.086.007
|View full text |Cite
|
Sign up to set email alerts
|

Transition Temperatures of the Hydrates of Na2SO4, Na2HPO4, and KF as Fixed Points in Biomedical Thermometry

Abstract: The hydrate transition temperatures of Na1S04 'IOH10 to Na1S04' KF· 2H10 to KF, and Na2HPO.· 7H20 to Na2HPO. '2H10 were established using AeS grade salts as 32.374 °e, 41.422 °e, and 48.222 °e, respectively. A simple and reliable procedure involving inexpensive materials was used to realize these transitions as temperature fixed points. Each transition temperature was attained within 30 minutes of hydrate initiation and remained constant to within ±0.002 °e for more than 10 hours if the mixture was stirred. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Suzuki et al(2010a) reported the latent heat transportation system with this hydrate slurry. Disodium hydrogen phosphate has several hydration structures as reported by Telkes (1980), Magin et al (1981) and Kenisarin and Mahvkamov (2016). In this study, the concentration of disodium hydrogen phosphate in water was set at 30 wt% as dodecahydrates of disodium hydrogen phosphate was obtained even in the cooling process.…”
Section: Materials and Experimental Details 21 Materialsmentioning
confidence: 60%
“…Suzuki et al(2010a) reported the latent heat transportation system with this hydrate slurry. Disodium hydrogen phosphate has several hydration structures as reported by Telkes (1980), Magin et al (1981) and Kenisarin and Mahvkamov (2016). In this study, the concentration of disodium hydrogen phosphate in water was set at 30 wt% as dodecahydrates of disodium hydrogen phosphate was obtained even in the cooling process.…”
Section: Materials and Experimental Details 21 Materialsmentioning
confidence: 60%
“…In this regard, the K 2 (H 2 O) 0,2,4 B 12 F 12 system resembles the K(H 2 O) 0,2,4 F system (i.e., KF·(H 2 O) 0,2,4 ) . The KF dihydrate crystallizes from aqueous solutions in the temperature range 19−41 °C, the tetrahydrate crystallizes at lower temperatures, and anhydrous KF crystallizes at temperatures above 41.4 °C . As we will discuss below, crystalline K 2 B 12 F 12 does not absorb water vapor to any extent above 52 °C.…”
Section: Resultsmentioning
confidence: 98%
“…86 The KF dihydrate crystallizes from aqueous solutions in the temperature range 19-41 °C, the tetrahydrate crystallizes at lower temperatures, and anhydrous KF crystallizes at temperatures above 41.4 °C. 87 As we will discuss below, crystalline K 2 B 12 F 12 does not absorb water vapor to any extent above 52 °C. DSC experiments revealed that the dehydration of crystalline K 2 (H 2 O) 2 B 12 F 12 in a stream of dry nitrogen was endothermic, with ∆H 298 ) 111(1) kJ mol -1 (the initial temperature was 25.0(5) °C).…”
Section: B Rapid and Irreversible Dehydration Of K 2 (H 2 O) 4 B 12 F 12mentioning
confidence: 93%
“…Non organic-Salt hydrates and metallic iii. Eutectics-it's a mixture of two or more component [71] There are lots of PCM available now days but its selection is very crucial thing [72]. It depends on the availability and applicability of the PCM of the selected purpose.…”
Section: Materials For Storage (Pcm)mentioning
confidence: 99%